Analysis of Agricultural Performance in Burkina Faso Using Data Envelopment Analysis (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we used the DEA method, to apply to the agriculture sector in BurkinaFaso. We applied the method with forty-one (41) agricultural farmers with data taking into account cultivated area, manual (human) labour, the liquidity fund of the working household, the number of crops (products) and the expected farm incomes. The results highlight the seven (7) technical efficiencies. Taking into account the variable scale yields, fourteen (14) efficient farms are obtained. These results show how non-efficient farms in the DEA sense are indexed to efficient farms that can serve as benchmarks or benchmarks in terms of performance improvement. This study shows that efficiency does not depend on the category of operator but on overall performance (efficiency and productivity).
Keywords: Farm performance indicators; Data Envelopment Analysis; productivity; technical efficiency; variable returns to scale; scale efficiency.